# calculus

posted by .

The equation x^2 y+2xy^3=8defines y as a function of x,y=f(x), near x=2, y=1.
a) Find dy/dx.

b) Now, find the slope of the curve
x^2y+2xy^3=8 when x=2, y=1.

• calculus -

differentiate implicitly,

x^2 + 2xy^3 = 8
2x + 2x(3y^2)dy/dx + 2(y^3) = 0

solve for dy/dx, then for b) sub in x=2, y=1

## Similar Questions

1. ### Calculus

The line that is normal to the curve x^2=2xy-3y^2=0 at(1,1) intersects the curve at what other point?
2. ### Calculus

Consider the equation: x^2 - 2xy + 4y^2 = 64 Write an expression of the slope of the curve at any point. (y^p)= y prime My work 2x - 2(xy^p + y) + 8yy^p = 0 2x -2xy^p - 2y + 8yy^p = 0 -2xy^p + 8yy^p = 2y -2x factored out y^p and then …
3. ### calculus

Find all points on the curve x^2y^2+xy=2 where the slope of tangent line is -1. This is what I got. x^2y^2+xy=2 x^2*2ydy/dx + 2x*y^2 + x*dy/dx + y =0 dy/dx(2yx^2+x)= -2xy^2-y dy/dx = (-2xy^2-y)/(x+2yx^2) how do I finish from here?
4. ### Calculus

Use implicit differentiation to find the slope of the tangent line to the curve –2x^2–2xy–1y^3=–3 at the point (–1–1).
5. ### Calculus

Use implicit differentiation to find the slope of the tangent line to the curve 2(x^2) + 2xy + 2(y^3)= -18
6. ### Calculus

find all points at the curve x^2y^2+2xy=3 with the slope of the tsngent is -1
7. ### calculus

Consider the curve defined by 2y^3+6X^2(y)- 12x^2 +6y=1 . a. Show that dy/dx= (4x-2xy)/(x^2+y^2+1) b. Write an equation of each horizontal tangent line to the curve. c. The line through the origin with slope -1 is tangent to the curve …
8. ### AP Calc

Find the equation of ALL horizontal tangents to the curve y^2=x^2+4/x, if any exists. My work: Derivative- First I multiply across and got x^2+4=xy^2 2x+0=(x)(2y(dy/dx)+(y^2) 2x-y^2=2xy(dy/dx) dy/dx=2x-y^2/2xy=x-y^2/xy I don't know …
9. ### calculus

Find the slope of the tangent line to the curve (2x+4y)^1/2+(2xy)^1/2=13.4 at the point (6,5).
10. ### ap calc

find the equation of all horizontal tangents to the curve y^2 = (x^2+4)/x, if any exist this is what I have so far: xy^2= x^2+4 2xydy/dx = 2x-y^2 dy/dx = (2x-y^2)/2xy (2x-Y^2)/2xy = 0 2x- Y^2 = 0 I don't know what to do after this

More Similar Questions